2011
DOI: 10.1007/s12311-011-0291-0
|View full text |Cite
|
Sign up to set email alerts
|

Torpedoes in the Cerebellar Vermis in Essential Tremor Cases vs. Controls

Abstract: The study of the postmortem changes in essential tremor (ET) is in its infancy, although recent evidence points to a central role of the cerebellum, where Purkinje cell axonal swellings ("torpedoes") are significantly more common in ET than control brains. Yet, all existing studies have been confined to the cerebellar hemispheres, and whether there is a more widely distributed cerebellar problem is presently unknown. Our aims were to address whether: (1) ET cases have greater numbers of torpedoes in the vermis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 58 publications
(84 reference statements)
3
40
0
Order By: Relevance
“…The volume of segments in a contiguous region of the vermis was reduced in the patient group, and there tended to be a greater reduction in volume in the cerebellar-ET group when compared with classic-ET group. This result is also compatible with recent pathological findings, which reported that the number of torpedoes in the cerebellar vermis was higher in ET patients when compared with controls [45].…”
Section: Discussionsupporting
confidence: 93%
“…The volume of segments in a contiguous region of the vermis was reduced in the patient group, and there tended to be a greater reduction in volume in the cerebellar-ET group when compared with classic-ET group. This result is also compatible with recent pathological findings, which reported that the number of torpedoes in the cerebellar vermis was higher in ET patients when compared with controls [45].…”
Section: Discussionsupporting
confidence: 93%
“…It is presumed to be secondary to dysfunction of the olivocerebellothalamic pathways [105], [106]. Although debated, relatively recent neuropathologic studies point towards Purkinje cell axonal swellings (“torpedoes”) in the cerebellar hemispheres and vermis as potential markers of disease [107]. …”
Section: - Alcohol Use In Patients With Movement Disorders: Essentiamentioning
confidence: 99%
“…The term “torpedo” was used to identify these focal swellings in 1918 by the Dutch psychiatrist Leendert Bouman (Bouman, 1918), and the term has been used since then to identify swellings or spheroids on Purkinje cell axons. Purkinje cell axonal torpedoes are observed in several diseases, including essential tremor (Louis et al, 2006, 2009, 2014), spinocerebellar ataxias (Sasaki et al, 1998; Yang et al, 2000; Louis et al, 2014), encephalopathy (Yagishita, 1978), and other cerebellar disorders (Hirano et al, 1973; Louis et al, 2014), and are especially prevalent in the cerebellar vermis (Louis et al, 2011). Torpedo-like swellings have also been observed in several spontaneously arising ataxic rodents, for e.g., weaver (Hirano et al, 1973), hyperspiny Purkinje cell (hpc) (Sotelo, 1990), and sticky mice (Sarna and Hawkes, 2011), groggy rats (Takeuchi et al, 1995), and in mouse models of disease such as Autosomal Recessive Ataxia of the Charlevoix-Saguenay Region (ARSACS) (Lariviere et al, 2015).…”
Section: Introductionmentioning
confidence: 99%